KARAKTERISTIK PAPAN KOMPOSIT DARI KULIT BAKAU, LIMBAH PLASTIK POLIPROPILENA, DAN PEREKAT UREA FORMALDEHIDA - Ramadhan, Kisfargi KB; Dirhamsyah, M; Husni, Harnani (JURNAL HUTAN LESTARI, 2018)
This research is aimed to know the effect composition of raw materials and concentration adhesives of urea formaldehyde to physical and mechanical properties composite board. Composite board made from the bakau bark, polypropylene plastic waste, and urea formaldehyde adhesive.  Variation ratio of bakau bark and polypropylene plastic were 60 : 40, 50 : 50, 40 : 60. The level of urea formaldehyde used thewere 10%, 12% and 14% of the total weigh of the composite board. Particle board is made with size 30 cm x 30 cm x 1 cm with target density of 0,7 g/cm3 at a specific pressure of 25 kg/cm2 and temperature of 220ºC for 10 minutes. Evaluation of the physical properties and mechanical properties was conducted according to JIS A 5908-2003. The results of this research showed the average value based the density is around 0,68 g/cm3 – 0,79 g/cm3, the moisture content is around 5,02 % -  6,84 %, thickness swelling is around 2,95 % - 4,18 %, water absorption is around 10,21 % - 19,22 %, modulus of elasticity is around 4990,46 kg/cm2 – 5780,79 kg/cm2, modulus of repture is around 104,73 kg/cm2 - 140,55 kg/cm2 , the internal bonding strength is around 7,53 kg/cm2 – 9,03 kg/cm2, and the screws holding strength is around 70,27 kg - 82,28 kg. The best treatment for the physical and mechanical of composite board made from ratio bakau bark and polypropylene plastic 40 : 60 and urea formaldehyde concentration 14%.Keyword: Bakau Bark, composite board, physical and mechanical properties, polypropylene plastic, urea formaldehyde